CFD modeling of a ducted Savonius wind turbine for the evaluation of the blockage effects on rotor performance. (October 2019) - Mauro, S.; Brusca, S.; Lanzafame, R.; Messina, M.
Abstract: The idea of investigating the fluid dynamic behavior of a ducted Savonius wind turbine derives from the research about the improvements of Oscillating Water Column Wave Energy Converters in which the air is forced to flow back and forth inside a duct. The Savonius rotors appeared to be very suitable for this kind of applications for many reasons. Indeed, these rotors are very simple to built, they are unidirectional respect to the incoming flow, they works well at low flow speed and they produce high torque which allow them to start at very low cut in velocities. By means of a CFD 2D numerical model, the present paper demonstrates the great potentialities offered by the use a Savonius wind turbine in Oscillating Water Column devices. The CFD model was developed and validated against experimental data, obtained in the subsonic wind tunnel owned by the University of Catania. The ducted rotor was simulated at different flow and rotational speed, in steady unidirectional condition which is of utmost importance as a first step in the more complex oscillating flow study. Highlights: The paper deals with the use of a ducted Savonius rotor for Oscillating Water Column Wave Energy Converters. A thorough description of the CFD 2D model is presented. The numerical model results are validated against experimental data. A brief description of the experimental set-up is shown. The ducted Savonius rotor appears to be very promising for the application in Oscillating Water Column systems.